Evaluation of some business macro environment forecasting methods - Kozlinskis, Vulfs; Guseva, Kristine (Journal of Business Economics and Management, 2006)
Latest studies in the field of business macro environment (BME) assessment and forecasting have been undertaken and successfully implemented by the World Bank (2003–2004). Considerable contribution to the field has been made by Nobel Prize winners in Economics F. Kydland and E. Prescott in 2004. Nonetheless, a number of issues concerning BME evaluation and forecasting is still left unstudied. The Article highlights two major issues of BME: the fist part of the paper is focused on assessment of BME and the quality of BME development prognosis made by entrepreneurs. Based on key findings the following second part of the research examines the accuracy (validity) of businessmen prognosis and identifies key indicators businessmen rely on for formulating their future expectations. For that purpose a system of parameters and trends, as well as entrepreneurs’ survey results have been applied. The study concludes by illustrating the effect of inaccurately formulated prognosis and expectation on further development of BME events in conjunction with new assessment and forecasting proposals.Firstd Published Online: 14 Oct 2010